Pengaruh Rasio Aktivitas Terhadap Return on Asset pada Perusahaan Industri Barang Konsumsi yang Terdaftar di Indeks Saham Syariah Indonesia - Zulkarnaini; Fata, Khairil; Yeni Irawan; Fakriah; Natami, Bella Aulia (JAKTABANGUN: Jurnal Akuntansi & Pembangunan, 2023)
This study aims to determine the effect of the Activity Ratio consisting of Total Asset Turnover, Receivable Turnover and Working Capital Turnover on Return on Assets in consumer goods industrial companies listed on the Indonesian Sharia Stock Index for the 2018-2020 period. The data used in this study is secondary data that is quantitative in nature using financial reports published on the Indonesia Stock Exchange. The population in this study were 49 issuers and the sample used in this study was 36 issuers using purposive sampling method. The model used in this study is the common effect panel data regression analysis, classical assumption test and hypothesis testing. The data processing was carried out using the Eviews8 analysis tool. The results of this study indicate that the Activity Ratio consisting of Total Asset Turnover, Receivable Turnover and Working Capital Turnover simultaneously has a significant effect on Return on Assets. And partially Total Asset Turnover, Receivable Turnover and Working Capital Turnover have a significant effect on Return on Assets in consumer goods industry companies listed on the Indonesian Sharia Stock Index